TINGKAT KEMATANGAN GONAD KEPITING BAKAU (Scylla serrata Forskal) DI HUTAN MANGROVE TELUK BUO KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Rahmi, Ennike Gusti; Sumarmin, Ramadhan; Zeswita, Armein Lusi (STKIP PGRI Sumbar, 2013)
ABSTRACT Brown Mud crab (Scylla serrata Forskal) living and perform spawning in Mangrove Forests. Gonad Maturity is a certain stage of gonadal development before and after spawning. The maturing gonadal development is part of reproduction before spawning occurs. This study was conducted to determine the Gonad Maturity of Brown Mud Crab (Scylla serrata Forskal) in the Buo Gulf Mangrove, Bungus, Teluk Kabung of Padang. The research was conducted in the month of May to July 2013 using the descriptive method through gonadal morphology observations Brown mud crab (Scylla serrata Forskal). the results showed female Brown Mud Crab recovered amounted to 72 individual. The percentage of the Month of May until July Gonad Maturity I: 8.33%, Gonad Maturity II: 16.67%, Gonad Maturity III: 16.67% Gonad Maturity IV: 13.89% Gonad Maturity V : 44.44%. Physic-chemical factor Waters measurement reports to temperature ranges from 28.4 to 31 ° C, pH 7-8, Salinitas water 32.3 to 34.5 ppm and depth of 50 cm-2 m.